ELECTRONIC TAX SERVICES AND CORPORATE TAXPAYER COMPLIANCE: AN EMPIRICAL STUDY OF E-REG, E-BILLING, E-BUPOT, E-FORM, AND E-FAKTUR - Jamilatul Qomariyah; Moh. Faisol (Journal of Accounting and Financial Issue (JAFIS), 2026)
Technological developments in the tax system have not fully changed taxpayers' behavior or compliance levels. Many taxpayers still carry out their obligations manually, even with assistance from third parties. This study aims to test the effect of e-reg, e-billing, e-bupot, e-form, and e-faktur on taxpayer compliance in Sumenep Regency. The data for this study were obtained using the Slovin sample technique, and then a research questionnaire was administered to collect responses. The data analysis used SPSS 26, and the results showed that e-reg, e-bupot, and e-faktur had a significant effect on taxpayer compliance, while e-billing and e-form had no effect. Meanwhile, the results of the F-test indicate that e-reg, e-billing, e-bupot, e-form, and e-faktur affect taxpayer compliance. This study's results imply that the technology used provides taxpayers with convenience in fulfilling their tax obligations, thereby increasing compliance. However, in the use of e-billing and e-forms, taxpayers revert to manual methods and depend on third parties.